Biomarker-Based Phase II Study of Sapanisertib (TAK-228): An mTORC1/2 Inhibitor in Patients With Refractory Metastatic Renal Cell Carcinoma. (16th February 2022) - McGregor, Bradley A.; Xie, Wanling; Adib, Elio; Stadler, Walter M.; Zakharia, Yousef; Alva, Aijai; Michaelson, M. Dror; Gupta, Shilpa; Lam, Elaine T.; Farah, Subrina; Nassar, Amin H.; Wei, Xiao X.; et al.
Abstract : PURPOSE: Sapanisertib is a kinase inhibitor that inhibits both mammalian target of rapamycin complex 1 (mTORC1) and mTORC2. In this multicenter, single-arm phase II trial, we evaluated the efficacy of sapanisertib in patients with treatment-refractory metastatic renal cell carcinoma (mRCC; NCT03097328 ). METHODS: Patients with mRCC of any histology progressing through standard therapy (including prior mTOR inhibitors) had baseline biopsy and received sapanisertib 30 mg by mouth once weekly until unacceptable toxicity or disease progression. The primary end point was objective response rate by RECIST 1.1. Tissue biomarkers of mTOR pathway activation were explored. RESULTS: We enrolled 38 patients with mRCC (clear cell = 28; variant histology = 10) between August 2017 and November 2019. Twenty-four (63%) had received ≥ 3 prior lines of therapy; 17 (45%) had received prior rapalog therapy. The median follow-up was 10.4 (range 1-27.4) months. Objective response rate was two of 38 (5.3%; 90% CI, 1 to 15.6); the median progression-free survival (PFS) was 2.5 months (95% CI, 1.8 to 3.7). Twelve patients (32%) developed treatment-related grade 3 adverse events, with no grade 4 or 5 toxicities. Alterations in the mTOR pathway genes were seen in 5 of 29 evaluable patients ( MTOR n = 1, PTEN n = 3, and TSC1 n = 1) with no association with response or PFS. Diminished or loss of PTEN expression by immunohistochemistry was seen in 8 of 21 patients and trended toward shorter PFS compared with intact PTEN (median 1.9 v 3.7 months; hazard ratio 2.5; 95% CI, 0.9 to 6.7; P = .055). CONCLUSION: Sapanisertib had minimal activity in treatment-refractory mRCC independent of mTOR pathway alterations. Additional therapeutic strategies are needed for patients with refractory mRCC. Abstract :